Targeted Inhibition of the PI3K/Akt/mTOR Signaling Axis: Potential for Sarcoma Therapy - Wani, Atif Khurshid; Singh, Reena; Akhtar, Nahid; Prakash, Ajit; Nepovimova, Eugenie; Oleksak, Patrik; Chrienova, Zofia; Alomar, Suliman; Chopra, Chirag; Kuca, Kamil (Mini Reviews in Medicinal Chemistry, 2024)
Sarcoma is a heterogeneous group of malignancies often resistant to conventional chemotherapy and radiation therapy. The phosphatidylinositol-3-kinase/ protein kinase B /mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathway has emerged as a critical cancer target due to its central role in regulating key cellular processes such as cell growth, proliferation, survival, and metabolism. Dysregulation of this pathway has been implicated in the development and progression of bone sarcomas (BS) and soft tissue sarcomas (STS). PI3K/Akt/mTOR inhibitors have shown promising preclinical and clinical activity in various cancers. These agents can inhibit the activation of PI3K, Akt, and mTOR, thereby reducing the downstream signaling events that promote tumor growth and survival. In addition, PI3K/Akt/mTOR inhibitors have been shown to enhance the efficacy of other anticancer therapies, such as chemotherapy and radiation therapy. The different types of PI3K/Akt/mTOR inhibitors vary in their specificity, potency, and side effect profiles and may be effective depending on the specific sarcoma type and stage. The molecular targeting of PI3K/Akt/mToR pathway using drugs, phytochemicals, nanomaterials (NMs), and microbe-derived molecules as Pan-PI3K inhibitors, selective PI3K inhibitors, and dual PI3K/mTOR inhibitors have been delineated. While there are still challenges to be addressed, the preclinical and clinical evidence suggests that these inhibitors may significantly improve patient outcomes. Further research is needed to understand the potential of these inhibitors as sarcoma therapeutics and to continue developing more selective and effective agents to meet the clinical needs of sarcoma patients.
Keywords: biomarkers